Analisis pemikiran Monzer Kahf Tentang Zakat dan Relevansinya Terhadap Penanggulangan Kemiskinan di Indonesia - Wydia Artanti; Tanesa Yulyanda; Tyas Nur’aini; Lina Marlina; Ana Fauziya Diyana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Poverty remains a fundamental problem rooted in Indonesia's socio-economic structure, despite various mitigation schemes implemented by the government. As the country with the largest Muslim population in the world, Indonesia has enormous sharia-based public financial resources, where zakat should be positioned as a strategic means of wealth distribution. However, in reality, this instrument is often not optimally realised in national macroeconomic policy. This study aims to analyse Monzer Kahf's Islamic economic thinking on zakat and its relevance to poverty alleviation efforts in Indonesia. The research method used is qualitative with a library research approach through a systematic literature review of Monzer Kahf's fundamental works and various studies related to national zakat management, which are analysed descriptively and analytically to connect the theoretical framework with the socio-religious dynamics in Indonesia.